MANAGEMENT DIRI DARI SUDUT PANDANG AL QUR’AN - Rima Dewi Setiani I; Sri Minarti (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Self Management plays a crusial role, to help the individuals reaching their objectives . Also given the significance, spesiaists have sought out techniques, frameworks, and theories to fulfill the goals established by management as a field of knowlegde, in fact, management has existed since the of humanity and is an integral aspect of daily life as individualss organize their existence. In Islam, guidance for management relies on the teachings of the Qur'an, serving as fundamental sources to address the challenges faced by Muslims. These teachings apply to all aspects of human life and activities, including the various forms of management discussed in the Qur’an and saying of the Prophet Muhammad. This paper will explore management from an Islamic perspective, based on the Qur'an, which will cover the definition of management, its functions (planning, organizing, executing, and controlling), and examine the skills and competencies required for effective leadership, all grounded in the teachings of the Qur'an and Hadith